STRATEGI PEMASARAN PRODUK BROADBAND INDIHOME PT TELKOM DI BEKASI (STUDI DESKRIPTIF KUALITATIF PADA AREA BEKASI) - Rutman Lumbantoruan; fernando Fernando; Fenny B.N.L. Tobing (Universitas Kristen Indonesia, 2026)
In this era of globalization, telecommunications have a significancy roles in human lifes. Along with change lifestyle of today societies, they need access to diverses, easily, faster, and reliable informations. Telecommunications service providers are competing increasingly tightly for the current development that makes PT Telkom Tbk innovation to issues the latest product by providing various communications facility to meeting need of community in telecommunication sectors of multiservice for its customers, namely voice services (telephones), data (internets) and images (IP-TV) on one access network and known for triple-play services. Marketing has a very significant role because marketing has positions as intermediary between producer and consumer. But Indihome lacks STP (Strategy, Targeting, and Positioning) because many middles to lower-class people object to Indihome's monthly price. Therefore, I conducted this research using the type of field researched, namely: research that aim to studies and understand intensive its currently backgrounds and environmentals interaction by social unit, individual, group, institution, or societies. Data analyst method use is descriptive analyst, conducted by requesting and collecting data in detail, which is original and asks directly to Internet Consumers, which I named Connected Internet Rumah in Bekasi. Data collections is through interview and documentations. Base on research result that have gone on, the marketing strategy for Indihome broadband products implemented by PT Telkom Bekasi area have been effectively in achieve an increased in Indihome user. Overall level of Indihome Customer Satisfaction is still relatively unsatisfied due to the lack of notification of information about internet usage to household customers who have a permanent home containing 5 to 8 people or household customers who do not has a permanently home and contract such as rented plots containing 3 to 5 people. The overall level of Indihome Customer Satisfaction is still relatively unsatisfied due to the lack of notification of information about internet usage to household customers who have a permanent home containing 5 to 8 people or household customers who do not has a permanently home and contract such as rented plots containing 3 to 5 people. Maybe in the future, I will create or propose an idea to work with Telkom Indonesia to create an Indihome subsidiary that can adjust to the needs of the middle to the lower-class community, such as to speed and effectiveness of users in a family or home. Keywords: Strategy, Satisfaction, Internet, Effectiveness